Political Alienation in Chinua Achebe’s A Man of the People - Shah, Saroj Kumar (Khwopa Journal, 2024)
This paper examines Chinua Achebe's A Man of the People, set in a post-colonial African nation, highlighting the social, political, and psychological impacts of European imperialism on indigenous African societies. In the novel, Achebe illustrates the political degradation in the country, where irresponsible and visionless leadership drives the nation into chaos, anarchy, and violence, hindering progress and prosperity. The novel explores how colonial remnants continue to invade and dominate the independent African homeland, leading to political alienation. Despite the end of colonial rule, psychological factors from imperialism persist, eroding the people's connection to their culture. Through the characters of Odili and political leader Nanga, Achebe portrays a limited and ineffective government, where neither the people nor the leaders show collective will or responsibility to revive the nation's cultural identity. As a result, people are unfamiliar with their culture and they are forced to live in a new form of slavery, pessimism and degeneration. Rather than having optimistic perspectives towards the decolonized independent nations, the self-glorifying dictators and their poverty, reflecting the harsh reality of post-colonial African nations, specifically Nigeria, struggle with the aftermath of colonialism in the form of corrupt leadership, identity crises, and political fragmentation showcasing the lingering effects of colonialism on Nigeria's political and cultural systems.